Redescription of Tyrus Aubé and T. sinensis Raffray (Coleoptera: Staphylinidae: Pselaphinae), and two new species from Sichuan, Southwest China - Yin, Zi-Wei; Nomura, Shûhei; Li, Li-Zhen (Zootaxa, 2013)
The genus Tyrus Aubé is redescribed with major diagnostic features illustrated. The first male specimen of T. sinensis Raffray (Type locality: Yunnan, China) is reported from Xizang, China, and two new species, Tyrus sichuanicus Yin & Nomura, sp. n. and Tyrus yajiangensis Yin & Li, sp. n., are described from Sichuan, China. All treated species are (re-)described, illustrated and distinguished.